End-of-life management of multiple myeloma patients in the era of CD38 and immunotherapy - Sesques, Pierre; Karlin, Lionel; Massy, Emmanuel; Maarek, Alizée; Aussedat, Guillaume; Lazareth, Anne; Golfier, Camille; Bouafia-Sauvy, Fadhela; Lequeu, Helene; Ghergus, Dana; Safar, Violaine; Ferrant, Emmanuelle; et al. (Frontiers in Oncology, 2024)
BackgroundIn spite of spectacular advances in the treatment of multiple myeloma, a majority of patients will die from this disease or related complications. While a great amount of focus has been dedicated to the development of novel therapies, little attention has been paid to latter stages of patient follow-up.Patients and methodsIn order to describe patient management during this critical period as well as the immediate causes and circumstances of death, we have analyzed a single center series of 100 patients diagnosed with myeloma who died between 2016 and 2021.ResultsPatients received a median of 3 lines of treatment, including 2 during their last year of life. Sixty per cent of patients had received daratumumab. Fifty patients had obtained complete remission or very good partial response at some time during the course of disease but 75 were refractory to the last treatment line. Eighteen patients died while their disease was stable or in remission while 77 had confirmed progressive disease at time of death. Thirty six patients had uncontrolled sepsis, 49 were in renal failure and 24 had hypercalcemia at the time of death. Seventy three patients presented with lymphopenia. Disease progression was documented in a majority of MM patients at the time of death and was associated with disease-related complications in a significant number of patients.ConclusionDisease progression remains the main cause of death in patients with multiple myeloma.